Phase-II Trials of Pazopanib in Metastatic Neuroendocrine Neoplasia (mNEN): A Systematic Review and Meta-Analysis - Bongiovanni, Alberto; Liverani, Chiara; Recine, Federica; Fausti, Valentina; Mercatali, Laura; Vagheggini, Alessandro; Spadazzi, Chiara; Miserocchi, Giacomo; Cocchi, Claudia; Di Menna, Giandomenico; De Vita, Alessandro; Severi, Stefano; et al. (Frontiers in Oncology, 2020)
Background: Several phase-II trials have been designed to evaluate tyrosine kinase inhibitors (TKIs), in particular, pazopanib in neuroendocrine neoplasia (NEN), but its efficacy has not yet been demonstrated in a randomised-controlled Phase III trial. A systematic review of the published clinical trials of metastatic NEN patients could reduce the possible bias of single phase II studies. The present systematic review focuses on the efficacy and safety of pazopanib in patients with metastatic and locally advanced NEN. Methods: A systematic search in the major databases Medline/PubMed, Cochrane and Embase and in supplementary material from important international Meetings was performed to identify publications on pazopanib for the treatment of neuroendocrine neoplasia. English language was defined as a restriction. Four authors of the present review independently performed the study selection, assessed the risk of bias and extracted study data. Four published clinical trials and 2 abstracts were identified. One trial was excluded because the topic was Von-Hippel Landau disease and one abstract was eliminated because of the lack of information on meeting proceedings. Results: In all of the trials pazopanib was orally administered at a dose of 800 mg daily continuously with a 28-day cycle. The intention-to-treat population for efficacy was composed of 230 patients with a median age of 62 years. The partial response rate was 10.7% (95% confidence interval 2.6–20.5). The rate for stable disease was 79.6% (range: 61.7–92.1%) with a disease control rate (DCR) of 90.3%. Progressive disease was reported in 9.7% (range 5.2–17.6) of patients. No complete responses were observed. Median progression-free survival was 11.6 months (95% CI: 9.2–13.9). Overall survival from all the trials was 24.6 (95% CI: 18.7–40.8) months. Severe adverse events (grade III–IV) included hypertension 31%, 16% increase in AST/ALT, diarrhoea 10% and fatigue 10%. Conclusions: Pazopanib monotherapy achieved a DCR of 90.3% in patients with locally advanced and/or metastatic neuroendocrine neoplasia, with an overall response rate comparable to other TKIs and mTOR inhibitors and a safety profile similar to that of drugs of the same class.